2D Catalysts for CO2 Photoreduction: Discussing Structure Efficiency Strategies and Prospects for Scaled Production Based on Current Progress. Issue 66 (29th September 2022) - Yang, Xiaohan; Li, Kai; Wang, Guangtao; Li, Xiang; Zhou, Pengyu; Ding, Shichao; Lyu, Zhaoyuan; Chang, Yu‐Chung; Zhou, Yuanzhen; Zhu, Wenlei
Abstract: Currently, the excessive consumption of fossil fuels is accompanied by massive emissions of CO2, leading to severe energy shortages and intensified global warming. It is of great significance to develop and use renewable clean energy while reducing the concentration of CO2 in the atmosphere. Photocatalytic technology is a promising strategy for carbon dioxide conversion. Clearly, the achievement of the above goals largely depends on the design and construction of catalysts. This review is mainly focused on the application of 2D materials for photocatalytic CO2 reduction. The contribution of synthetic strategies to their structure and performance is emphasized. Finally, the current challenges, and prospects of 2D materials for photoreduction of CO2 with high efficiency, even for practical applications are discussed. It is hoped that this review can provide some guidance for the rational design, controllable synthesis of 2D materials, and their application for efficient photocatalytic CO2 reduction. Abstract : A 2D view of photocatalysis : This review discusses 2D materials with excellent performance in photocatalytic CO2 reduction, summarizes existing synthetic strategies, and highlights promising batch preparation strategies. Second, our work summarizes the existing applications and modification strategies of various 2D materials in the field of CO2 emission reduction.